IPO 저가발행이 이후공모에 미치는 영향 - 송치승(Chi-Seung Song); 전진규(Jin Q Jeon) (한국증권학회지, 2019)
IPO 저가발행의 원인에 대하여 매우 다양한 이론적 및 실증적 연구가 진행되어 왔다. 이 중 저가발행신호이론에 따르면 정보비대칭 상황에서 IPO 저가발행은 이 발행기업이 우량기업이라는 신호를 시장에전달하는 수단이며, 저가발행을 통해 향후 필요 자본을 더 좋은 조건으로 조달할 수 있다. 본 연구는2000년부터 2015년까지 코스닥 IPO를 대상으로 저가발행과 이후공모와의 관련성을 분석하여 저가발행신호효과 가설을 검증하였다. 국내 가격제한폭제도를 고려하여 저가발행을 공모가 대비 상장당일종가수익률과 상장 이후 10일, 20일 및 30일 수익률을 사용하였다. 분석결과 저가발행은 발행기업의IPO 이후 주식 또는 채권공모 가능성을 유의하게 높이는 것으로 나타나 신호효과가 국내 IPO 시장에서존재한다는 것을 증명하였다. 이와 같은 결과는 내생성을 통제한 후 그리고 벤처캐피탈의 인증효과를통제한 후에도 존재하는 것으로 나타났다. 그러나 저가발행이 이후공모규모와 이후공모까지의 소요기간에 미치는 영향은 강한 유의성을 보이지 않았다. 본 연구는 국내 연구로는 최초로 저가발행 신호효과에대하여 실증연구이며, 저가발행이 이후공모 가능성을 높이나 공모규모와 소요기간에는 유의적 영향을미치지 않는다는 결론은 학문적 및 실무적으로 시사하는 바가 클 것으로 기대한다. According to IPO signaling theory, IPO underpricing is used under information asymme-try, where an issuing firm has better information on firm quality to signal the firm’s true value. This signaling is costly, but may enable the firm to return to the market and sell se-curities on better terms at a later date. The empirical implications of IPO signaling theory is that underpricing has a favorable and significant effect on the probability, size, and speed of subsequent security offerings. This study examines IPO signaling theory using an IPO sample in the KOSDAQ market. We consider the upper or lower price limit in Korea and define underpricing as the first-day return as well as the 10-day and 20-day return after IPOs. We examine the IPO samples in the KOSDAQ market to find that, consistent with the signaling theory, underpricing significantly increases the probability of seasoned securities. This result holds when we estimate the instrumental variable probit model and control for endogeneity. However, we find that the size and period taken for seasoned offerings are not significantly correlated with underpricing. The contribution of this study to the IPO literature is that it is the first study to investigate IPO signaling theory in the Korean market. Furthermore, the finding that underpricing is statistically correlated with the probability of seasoned securities offerings but not statistically correlated with the size and time of such offerings has important academic and practical implications. KCI Citation Count: 0